Functional Polymers and Polymer–Dye Composites for Food Sensing. Issue 21 (25th August 2020) - Zhang, Hang; Chan‐Park, Mary B.; Wang, Mingfeng
Abstract: The sensitive, safe, and portable detection of food spoilage is becoming unprecedentedly important because it is closely related to the public health and economic development, particularly given the globalization of food supply chain. However, the existing approaches for food monitoring are still limited to meet these requirements. To address this challenge, much research has been done to develop an ideal food sensor that can indicate food quality in real‐time in a sensitive and reliable way. So far, many sensors such as time–temperature indicators, smart trademarks, colorimetric tags, electronic noses, and electronic tongues, have been developed and even commercialized. In this feature article, the recent progress of food sensors based on functional polymers, including the molecular design of polymer structures, sensing mechanisms, and relevant processing techniques to fabricate a variety of food sensor devices is reviewed. Abstract : In this feature article, the recent progress on the design and fabrication of functional polymer‐based sensors for monitoring food spoilage is reviewed. Functional polymeric systems, including polymer‐dye composites, π‐conjugated polymers, polymers with aggregation‐induced emission, and polymer‐grafted surfaces, have shown great potential for the development of food sensors.